2021
DOI: 10.1039/d1tb01147b
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible dextran-coated gadolinium-doped cerium oxide nanoparticles as MRI contrast agents with high T1 relaxivity and selective cytotoxicity to cancer cells

Abstract: Gd-based complexes are widely used as magnetic resonance imaging (MRI) contrast agents. The safety of previously approved contrast agents is questionable and is being re-assessed. The main causes of concern...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…Nuclear medicine imaging has the highest sensitivity (pM range) and quantitative property, but suffers from a poor spatial resolution (mm range) [ 170 ]; CT excels at rapid image acquisition and facile three-dimensional (3D) reconstruction, but has limited resolution in soft tissues [ 171 ]; MRI has a high spatial resolution and excellent soft-tissue contrast with the versatility to provide information regarding tissue metabolism and perfusion. However, MRI suffers from lower sensitivity and hence requires a higher contrast agent dose to achieve necessary resolution [ 172 ], although recent advances in nanotheranostics have enhanced the per particle and per metal ion relaxivity [ 173 , 174 ]. It is also challenging to perform whole-body assessment using MRI and US, and therefore it is foreseeable nuclear imaging will remain as the quantitative whole-body approach in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear medicine imaging has the highest sensitivity (pM range) and quantitative property, but suffers from a poor spatial resolution (mm range) [ 170 ]; CT excels at rapid image acquisition and facile three-dimensional (3D) reconstruction, but has limited resolution in soft tissues [ 171 ]; MRI has a high spatial resolution and excellent soft-tissue contrast with the versatility to provide information regarding tissue metabolism and perfusion. However, MRI suffers from lower sensitivity and hence requires a higher contrast agent dose to achieve necessary resolution [ 172 ], although recent advances in nanotheranostics have enhanced the per particle and per metal ion relaxivity [ 173 , 174 ]. It is also challenging to perform whole-body assessment using MRI and US, and therefore it is foreseeable nuclear imaging will remain as the quantitative whole-body approach in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…They are quite promising as they are effectively endocytosed by normal and cancerous human cells. As well, they demonstrate dose‐dependent selective cytotoxicity to cancerous cells 68 …”
Section: Future Perspectivesmentioning
confidence: 96%
“…As well, they demonstrate dose-dependent selective cytotoxicity to cancerous cells. 68 Specific targeting of CeO 2 NPs to the diseased tissue could also enhance the therapeutic activity and improve the pharmacokinetics of the NPs. A recent research has revealed that active targeting accomplished by the decoration of hyaluronic acid on the surface of CePEI-NPs resulted in significant increase in breast cancer cell uptake.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In the authors’ previous studies, a proposal was made for the design of new Gd-based MRI contrast agents based on nanocrystalline Gd-doped ceria [ 6 , 7 , 8 , 9 ]. In an oxide matrix, Gd 3+ ions can provide higher values of longitudinal relaxation constants than Gd 3+ in chelate complexes.…”
Section: Introductionmentioning
confidence: 99%